The role of the microscale contact line dynamics in the wetting behaviour of complex fluids - Biolè, D.; Bertola, V. (Archives of Mechanics, 2015)
The microscale morphology of the liquid-substrate contact line is studied experimentally in two well-known examples of dynamic wetting with complex fluids (namely, drop impact of dilute polymer solutions and spreading of superspreader surfactant solutions). High-speed, high-magnification images of the contact line details were obtained using a high-frame rate camera equipped with a digital microscope zoom lens. Unlike in the case of simple liquids, which exhibit a smooth contact line, the advancing or receding contact line of complex fluids shows peculiar transient features which extend significantly in the radial direction (perpendicular to the contact line itself). It is argued such microscopic features determine the macroscopic dynamic wetting behaviour of complex fluids.